2016
DOI: 10.24059/olj.v20i1.565
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Previous Online Course Experience on Students' Perceptions of Quality

Abstract: The purpose of this paper is to explore whether experienced online students (who have completed seven or more online courses) perceive the quality of their courses differently than novice online students (who have completed three or fewer online courses) or students with an intermediate level of online course experience (those who have completed four to six online courses). Overall, 3,160 online students completed a survey which asked them to indicate the extent to which statements derived from the Quality Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 31 publications
(26 reference statements)
1
28
0
Order By: Relevance
“…Prior research on expert and novice online faculty has mainly focused on studying expert, exemplary, or experienced instructors and their teaching practices (Hixon, Barczyk, Ralston-Berg, & Buckenmeyer, 2016). Lewis and Abdul-Hamid (2006) studied exemplary online faculty's teaching to find that they were organized, fostered interaction, provided timely feedback, facilitated learning, and maintained student enthusiasm.…”
Section: Expert and Novice Online Instructorsmentioning
confidence: 99%
“…Prior research on expert and novice online faculty has mainly focused on studying expert, exemplary, or experienced instructors and their teaching practices (Hixon, Barczyk, Ralston-Berg, & Buckenmeyer, 2016). Lewis and Abdul-Hamid (2006) studied exemplary online faculty's teaching to find that they were organized, fostered interaction, provided timely feedback, facilitated learning, and maintained student enthusiasm.…”
Section: Expert and Novice Online Instructorsmentioning
confidence: 99%
“…Our literature review suggests that rubrics for measuring course quality have been validated mostly in terms of the opinions and perceptions of faculty and students, rather than in terms of construct validity or relationships to learning outcomes (Hixon, Barczyk, Ralston-Berg, & Buckenmeyer, 2016). Empirical studies (Jaggars & Xu, 2016;Lee, 2014;Liu et al, 2010;Sun et al, 2008;Swan et al, 2012) have found that a course with high quality scores measured by rubrics resulted in higher student learning outcomes in terms of course performance or satisfaction than one receiving low quality scores.…”
Section: Course Quality and Student Learning Outcomesmentioning
confidence: 99%
“…One major issue in early research of online learning is concerned with perceptions of students in higher education (Armstrong, 2011;Artino, 2010;Astani et al, 2010). Some studies specifically compared the perceptions of experienced and novice online students (Hixon et al, 2016) while others examine the difference between faculty and students" perception of online classes (Bagasra & Mackinem, 2019). Some attempts have been made to evaluate the quality of digital tools to be used in online courses (Rogers, 2011).…”
Section: Introductionmentioning
confidence: 99%